Learning while doing practical robotics education. - Nagai, K.
The students of today are likely to see current advanced products as black boxes. However, trying to open the black boxes is crucially important for the students who are going to be researchers or technical experts. Based on this idea, the curriculum of our department concerning practical robotics education was planned to cultivate the fundamental spirit of students for designing/manufacturing valuable products. In the article, first the basic concepts of practical engineering education are presented. Second, the outline of classes for practical education at the Department of Robotics in Ritsumeikan University are described, including experiments in robotics using 3 degree-of-freedom (DOF) and 6-DOF manipulators and practices of robot making. Then, practical education for a cooperative academia-industry environment is described. Such an education should contribute to the production of valuable products and to the transfer of advanced technologies to industry
Keywords: Department of Robotics; Ritsumeikan University; Advanced products; Cooperative academia-industry environment; Practical engineering education; Practical robotics education